IMPLEMENTASI BAHAN AJAR ETIKA KRISTEN BERDASARKAN MODEL DESAIN ADDIE - Adolfina Putnarubun; Geneton Hully (Nusantara Hasana Journal, 2024)
Students are adult learners, who have practical and critical thinking in the learning process. So teachers, in this case lecturers, have an important role in creating a comfortable learning situation, so that students do not learn under pressure. Effective and efficient learning certainly has a very good influence on students' development in learning. To create good learning, a teacher needs to equip himself with various kinds of learning models and continue to develop these learning models according to the context of the students. Comfortable and enjoyable learning is the dream of today's students, this certainly provides strong encouragement to every lecturer to be able to develop themselves and continue to follow developments in students' learning methods. Students cannot be seen as students who don't know many things, instead students can be used as discussion partners for lecturers in designing interesting learning. The ADDIE learning model is a learning model that can be used in designing Christian Ethics learning in higher education. There are five stages in the ADDIE learning model, namely Analyze, Design, Develop, Implement and Evaluate. Some of these stages or steps are carried out procedurally, there are instructional design models that are not procedural or cyclical or can start from a certain stage, and there are also integrative learning design models.